Does Veteran Status Mitigate Racial Disparities in Prostate Cancer Screening? Analysis of Prostate Specific Antigen Screening Patterns in the 2018 Behavioral Risk Factor Surveillance System Data. Issue 5 (30th May 2022) - Alkhatib, Khalid; Labban, Muhieddine; Briggs, Logan; Nguyen, David-Dan; Herzog, Peter; Cole, Alexander P.; Haag, Austin; Trinh, Quoc-Dien
Abstract : Purpose: We examined the effect of veteran status on prostate specific antigen (PSA) screening and whether health coverage available to veterans mitigates racial disparities in PSA screening. Materials and Methods: We conducted a cross-sectional analysis of non-Hispanic White (NHW) and non-Hispanic Black (NHB) men aged between 55 and 69 years who responded to the PSA screening survey in the 2018 Behavioral Risk Factor Surveillance System data. Complex weighted logistic regression models were used to evaluate predictors of PSA screening. Results: Screening prevalence was 43% in veterans (95% CI 42%–45%) versus 40% in nonveterans (95% CI 39%–40%, p <0.001). Among nonveterans, the prevalence of PSA screening was significantly lower in NHB (34%, 95% CI 31%–37%) versus NHW men (40%, 95% CI 39%–41%, p <0.001). Among veterans, NHB men had a significantly higher screening prevalence (48%, 95% CI 43%–54%) versus NHW men (42%, 95% CI 41%–44%, p=0.04). In adjusted analysis, veteran status (OR 1.11, 95% CI 1.01–1.21, p=0.02) and NHB race (OR 1.29, 95% CI 1.12–1.48, p <0.001) were significantly associated with receipt of PSA screening. Given that we found an interaction between veteran status and race (pint =0.03), a marginal analysis was performed. Compared to NHB nonveterans, NHB veterans had higher odds of undergoing PSA screening (OR 1.46, 95% CI 1.11–1.91, p=0.01). However, this association was not demonstrated when comparing NHW veterans versus nonveterans (OR 1.06, CI 0.97–1.16, p=0.22). Conclusions: Veteran status and NHB race were found to be independent predictors of PSA screening. The interaction between veteran status and race suggests that access to health coverage available to veterans may mitigate racial differences in prostate cancer screening behaviors. Further studies are needed to translate such findings into the civilian health care system.